Exploring Path Models of Disablement in Residential Care and Assisted Living Residents. (December 2018) - Phillips, Lorraine J.; Petroski, Gregory F.; Conn, Vicki S.; Brown, Marybeth; Leary, Emily; Teri, Linda; Zimmerman, Sheryl
This study examined the relationships between individual and environmental factors and physical activity, and between physical activity and functional limitations and disability in residential care/assisted living (RC/AL) residents. Participants completed questionnaires and physical performance tests, and wore the Fitbit Motion Tracker® to capture physical activity. Model fit was analyzed using two-level path models with residents nested within RC/AL settings. Model parameters were estimated using the MPlus robust maximum likelihood method. A multilevel model with good fit (root mean square error of approximation = 0.07, comparative fit index [CFI] = 0.91) showed that persons with greater exercise self-efficacy were more physically active, and persons who were more physically active had better physical function and less disability. Setting-level factors did not significantly correlate with physical activity or disability. Although environmental factors may influence physical activity behavior, only individual factors were associated with physical activity in this sample of RC/AL residents.